Lifeshocks : And How to love them - Sabbage, Sophie
Sophie Sabbage was diagnosed with late stage 'incurable' lung cancer in October 2014. She was 48 years old, happily married with a 4-year-old daughter. Since that day - when doctors told Sophie that her prognosis was poor - she has been on a remarkable